Electronic Noses for Biomedical Applications and Environmental Monitoring - Lozano, Jesus (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book, titled "Electronic Noses for Biomedical Applications and Environmental Monitoring", includes original research works and reviews concerning the use of electronic nose technology in two of the more useful and interesting fields related to chemical compounds detection of gases. Authors have explained their latest research work, including different gas sensors and materials based on nanotechnology and novel applications of electronic noses for the detection of diverse diseases. Some reviews related to disease detection through breath analysis, odor monitoring systems standardization, and seawater quality monitoring are also included.